Dose‐Independent Transfection of Hydrophobized Polyplexes. Issue 25 (14th May 2021) - Zhang, Zhen; Qiu, Nasha; Wu, Shuling; Liu, Xin; Zhou, Zhuxian; Tang, Jianbin; Liu, Yanpeng; Zhou, Ruhong; Shen, Youqing
Abstract: Cationic polymers dynamically complex DNA into complexes (polyplexes). So, upon dilution, polyplexes easily dissociate and lose transfection ability, limiting their in vivo systemic gene delivery. Herein, it is found that polyplex's stability and endocytosis pathway determine its transfection dose‐dependence. The polyplexes of hydrophilic polycations have dose‐dependent integrity and lysosome‐trafficking endocytosis; at low doses, most of these polyplexes dissociate, and the remaining few are internalized and trapped in lysosomes, abolishing their transfection ability. In contrast, the polyplexes of the polycations with optimal hydrophobicity remain integrated even at low concentrations and enter cells via macropinocytosis directly into the cytosol evading lysosomes, so each polyplex can accomplish its infection process, leading to dose‐independent DNA transfection like viral vectors. Furthermore, the tuned hydrophobicity balancing the affinity of anionic poly(γ‐glutamic acid) (γ‐PGA) to the polyplex surface enables γ‐PGA to stick on the polyplex surface as a shielding layer but peel off on the cell membrane to release the naked polyplexes for dose‐independent transfection. These findings may provide guidelines for developing polyplexes that mimick a viral vector's dose‐independent transfection for effective in vivo gene delivery. Abstract : Unlike viral vectors that are capable of individual transfection, dynamically complexed cationic polymers/DNA nanoparticles (i.e., polyplexes) dissociate and thus lose transfection ability at reduced concentrations, causing in vivo transfection inefficiency once systemically administered. Optimizing the polymer hydrophobicity is shown to integrate the polyplexes upon dilution and enter cells via macropinocytosis, leading to virus‐mimicking dose‐independent DNA transfection.